Graphenide Solutions: A Chemical Platform for Nanoparticle–Nanocarbon Composites. Issue 61 (5th October 2018) - Hof, Ferdinand; Pénicaud, Alain
Abstract: Graphenide solutions, comprising charged graphene layers in aprotic organic solutions, are exploited as a chemical platform to graft transition‐metal oxide nanoparticles, namely nickel, manganese, copper, and cobalt oxide, onto the carbon framework. The reduction process is driven and controlled by the graphenide solution yielding nanoparticles with comparable sizes for all studied metal salts, well below 10 nm. The synthesis is generic and is not limited by the type of metal salt, because the reduced graphene layers serve simultaneously as both substrates and reducing agents. This reaction is reliable, reproducible, and versatile, generating materials for catalytic purposes without requiring any kind of stabilization or capping agents. Abstract : Graphenide solutions have been exploited to generate transition‐metal oxide nanoparticles directly grafted onto the carbon framework. By only varying the metal precursor in the synthesis, nanoparticles smaller than 10 nm are generated and these are highly sought‐after for catalytic purposes.